Clinical utility of C‐terminal telopeptide of type 1 collagen in multiple myeloma. (20th January 2016) - Ting, Kay R.; Brady, Jennifer J.; Hameed, Abdul; Le, Giao; Meiller, Justine; Verburgh, Estelle; Bayers, Christopher; Benjamin, Dalia; Anderson, Kenneth C.; Richardson, Paul G.; Dowling, Paul; Clynes, Martin; et al.
Summary: Myeloma bone disease (MBD) is a major cause of morbidity in multiple myeloma (MM). We investigated bone turnover markers (BTM) as relapse predictors and biomarkers for monitoring MBD. We measured C‐terminal telopeptide of type I collagen (CTX‐1), and Procollagen type 1 N Propeptide (P1NP) in 86 MM patients and 26 controls. CTX‐1 was higher in newly diagnosed patients compared to control, remission and relapse ( P  < 0·05), and decreased following treatment. In the setting of relapse, a CTX‐1 rise greater than the calculated least significant change (LSC) was observed in 26% of patients 3–6 months prior to relapse ( P  = 0·007), and in 60·8% up to 3 months before relapse ( P  = 0·015). Statistically significant changes in CTX‐1 levels were also observed in patients who were with and without bisphosphonate therapy at the time of relapse. In patients with normal renal function, mean CTX‐1 level was highest in the newly diagnosed group (0·771 ± 0·400 μg/l), and lowest in the remission group (0·099 ± 0·070 μg/l) ( P  < 0·0001). P1NP levels were not statistically different across the patient groups. We conclude that CTX‐1, measured on an automated hospital laboratory platform, has a role in routine treatment monitoring and predicting relapse of MBD, even in patients on bisphosphonates.